1. y = 5 - 3x

Set this into (-2x + 3y = 4)

-2x + 3(5 - 3x) = 4

-2x + 15 - 9x = 4

-11x = -11

x = 1

Set x = 1 into (y = 5 - 3x)

y = 5 - 3(1)

y = 2

---------------------------------

2. y = 5x

Set y = 5x into the 2nd equation (2x + y = 28)

2x + 5x = 28

x = 4

Set x = 4 into the 1st equation

y = 5(4) = 20

----------------------------------

3. x + 3y = 23

x = 23 - 3y

Set into 2nd equation(3x - 2y = 3)

3(23 - 3y) - 2y = 3

69 - 9y - 2y = 3

-11y = -66

Thus y = 6

Set y = 6 into 1st equation

x + 3(6) = 23

x = 5

------------------------------------

4. x = 1/5y

3x + 2y = 26

Set (x = 1/5y) into 2nd equation

3(1/5y) + 2y = 26

3/5y + 2y = 26

3y + 10y + 130

13y = 130

y = 10

Set y = 10 into 1st equation

x = 1/5 x 10

x = 2

------------------------------------------------

Hope this helps....